QUANTITATIVE FEATURES OF FINGER DERMATOGLYPHICS AS MARKERS OF ATOPIC DERMATITIS, BRONCHIAL ASTHMA AND ALLERGIC RHINITIS - Dmytrenko, S.V.; Shcherba, I.K.; Ocheretna, N.P.; Kulchevich, L.V.; Fik, L.O. (World of Medicine and Biology, 2019)
Comorbidity of atopic diseases has become the basis for the application of the method of dermatoglyphics to clarify the genetic nature of the "atopic march". The purpose of the study is to identify differences in the quantitative features of finger dermatoglyphics between patients with atopic dermatitis, allergic rhinitis and bronchial asthma. Primary indices of finger dermatoglyphics of patients with atopic dermatitis, allergic rhinitis and bronchial asthma of young men and young women are taken from the data bank of National Pirogov Memorial Medical University, Vinnytsya, and have been used in previous studies in comparison with almost healthy young men and young women. Imprints were obtained by the method of “printing ink” by Gladkova T.D. By the method of Cummins H. and Midlo Ch. dermatoglyphic study of 320 young men and young women with allergic rhinitis (n=69), bronchial asthma (n=108) and atopic dermatitis (n=143) was performed. The quantitative indices of finger dermatoglyphics were analyzed: finger ridge count, summary and total ridge count and delta index. Statistical processing of the results was carried out in the package “Statistica 6.1”. It is established that the differences of quantitative finger dermatoglyphics indices between young men or young women with atopic dermatitis and allergic rhinitis cover respectively 0 % and 35.71 %, between patients with allergic rhinitis and bronchial asthma – 28.57 % and 42.86 %, respectively, patients with atopic dermatitis and bronchial asthma – 42.86 % and 100 % respectively. The results obtained determine the order of the "atopic march" development: atopic dermatitis or allergic rhinitis → bronchial asthma (in young men); atopic dermatitis → allergic rhinitis → bronchial asthma (in young women).